PERANCANGAN MEDIA PROMOSI EKOWISATA MANGROVE WONOREJO SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Laziem, Syarful; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract: Ecotourism Mangrove Wonorejo is one of the sites that have potential in the city of Surabaya. Mangrove Wonorejo also has the potential of natural beauty and cultural wealth of high value in the market Ecotourism industry. The problem is less widely known as other tourist. In terms of promotion, this time Mangrove Wonorejo only carry out promotional activities in the form of banners and only installed around the sights alone. In addition, a website designed Mangrove Wonorejo not much visited by visitors. This resulted in information about Ecotourism Mangrove Wonorejo less known by the public. The purpose of this research is directed at designing a media campaign Ecotourism Mangrove Wonorejo to increase brand awareness. So from this problems takes some effort to increase brand awareness, one of which is to design the appropriate media campaign for Ecotourism Mangrove Wonorejo who can provide information to the public to increase brand awareness in place Ecotourism Mangrove Wonorejo.Â Keywords: Design, Eco-tourism, Brand Awareness.